Survey Kondisi Fisik dan Teknik Dasar Sepak Bola Usia 10-12 Tahun pada Pemain SSB Se-Kecamatan Karanganyar Tahun 2026 - Andri Anggoro Saputro; Fatkhul Imron; Risa Agus Teguh Wibowo (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to determine the level of physical condition and basic football technical skills of 10–12-year-old players enrolled in Football Schools (SSBs) across Karanganyar District in 2026. The study involved 50 athletes selected using a purposive sampling technique. Data were collected through a series of standardized tests, including physical condition assessments (50-meter sprint, vertical jump, sit-up, pull-up, and 1,000-meter run) and basic football technical skill tests (passing and stopping, heading, dribbling, and shooting). Data were analyzed using descriptive quantitative statistics with percentage analysis. The results indicated that, in terms of physical condition, 5 athletes (10%) were categorized as excellent, 41 athletes (82%) as good, and 4 athletes (8%) as fair. Overall, the players' physical condition was classified as good. Meanwhile, the assessment of basic football technical skills revealed that 5 athletes (10%) were categorized as excellent, 10 athletes (20%) as good, 20 athletes (40%) as fair, 11 athletes (22%) as poor, and 4 athletes (8%) as very poor. Based on the overall mean score, the players' basic football technical skill level was classified as fair. The findings indicate a gap between the players' relatively good physical condition and their moderate mastery of basic football techniques, highlighting the need for more structured and integrated technical training programs.